2014
DOI: 10.1097/sla.0b013e31828e7602
|View full text |Cite
|
Sign up to set email alerts
|

Pudendal Nerve Stimulation for Bowel Dysfunction in Complete Cauda Equina Syndrome

Abstract: PNS is an effective treatment in the short term for bowel dysfunction in some patients with complete CES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Evidently, the postoperative anorectal function must also be examined in detail. It is well known that the PVs provide the majority sensations and functions of the anorectum [28]. In our preliminary study using dogs, anorectal function recovery could be observed at six months after re-anastomoses of the PVs (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…Evidently, the postoperative anorectal function must also be examined in detail. It is well known that the PVs provide the majority sensations and functions of the anorectum [28]. In our preliminary study using dogs, anorectal function recovery could be observed at six months after re-anastomoses of the PVs (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…Pudendal nerve stimulation in cauda equina subjects was investigated in a recent study with promising results. 20 Other treatment modalities of interest are posterior tibial nerve stimulation, dorsal genital nerve stimulation and magnetic stimulation. 19 Other aspects which may have limited the use of SARS are a long learning curve to perform the surgical procedure, subject selection, knowledge on stimulator setup, troubleshooting when errors occur and known complications to the surgical procedure (cerebrospinal fluid leakage and infection).…”
Section: Discussionmentioning
confidence: 99%
“…It also impacts on the anal muscles and causes fecal incontinence, impotence and insensibility in the saddle area. Acute symptoms of this syndrome include pain in the leg and severe back pain and strict sense changes in saddle shaped area (genitals, urethra, anus, inner tights) like urinary retention and incontinence that need for hospitalization (8-11). This syndrome is classified into two types of complete (or CES with true retention; CESR) and incomplete (incomplete CES; CESI).…”
Section: Introductionmentioning
confidence: 99%